Can Dermoscopy Be a Useful Follow-Up Tool in Patients with Discoid Lupus Treated with Anifrolumab? - Francesca Ambrogio; Caterina Foti; Silvia Noviello; Gerardo Cazzato; Alexandre Raphael Meduri; Carolina Marasco; Angelo Vacca; Benedetta Tirone (Diagnostics)
This report discusses a female patient with longstanding discoid lupus erythematosus (DLE) and systemic lupus erythematosus (SLE), refractory to multiple immunosuppressive and biologic treatments. Upon presenting with infiltrated, hypertrophic plaques in facial and décolletage regions, she was started on anifrolumab therapy after the histopathological confirmation of DLE. Following three infusions, significant clinical and dermoscopic improvements were observed, including the resolution of plaques and regression of scarring areas. This case highlights anifrolumab’s efficacy in severe lupus skin manifestations, emphasizing its potential to induce dermoscopic and histological remission. Additionally, it suggests that dermoscopy could be a valuable tool for monitoring therapeutic responses in DLE and cutaneous lupus erythematosus, warranting further investigation.